Perencanaan Balai Pengajian TPA An Nur di Desa Lambada Peukan, Kecamatan Darussalam, Kabupaten Aceh Besar - Fuady, Mirza; Ridwan, Nasrullah; Buraida, Buraida; Munadi, Rizal (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2024)
Community service activities in the form of Planning for the Taman Pendidikan Alquran (TPA) An-Nur Study Center, aim to provide TPA supporting facility planning services by making drawings of the study center plan and cost budget plan for the implementation of its construction. The target audience in this community service activity is the manager of the TPA An-Nur in Lambada Peukan Village. The stage of data collection for planning begins with an interview on the needs of facilities and observation of the introduction of existing conditions at the planning site. The interview method is used to obtain information on the condition of existing facilities and the needs of facilities needed for the future. Furthermore, the data collected is processed into concepts and plan drawings. Meanwhile, in the final stage, a cost budget plan is made for the implementation of the planned facility construction. The benefits obtained from this community service activity are the production of a drawing document of the plan of the TPA An-Nur Study Center and a budget plan for its construction costs, making it easier for managers to follow up on the construction stage of the TPA An-Nur facility.